Effects of alkyl chain length on the interfacial, antibacterial, and antioxidative properties of erythorbyl fatty acid esters. (15th January 2023) - Kim, Jihoon; Yu, Hyunjong; Yang, Eunhye; Choi, Yoonseok; Chang, Pahn-Shick
Abstract: Erythorbyl fatty acid esters (EFEs) are promising multifunctional food emulsifiers with antibacterial and antioxidative activities. Variations in the alkyl chain of EFEs may alter the physicochemical properties, affecting their multifunctional characteristics. Herein, the effect of alkyl chain length of EFEs on the multifunctionality was investigated by comparing the interfacial, antibacterial, and antioxidative activities of homologous series of EFEs with different saturated fatty acids (C10:0-C18:0). Interfacial tension measurement indicated that critical micelle concentration (CMC) decreased with increasing alkyl chain length, and erythorbyl myristate (EM, C14:0) with CMC of 1.2 mM and γCMC of 1.4 mN/m had the best interfacial properties among EFEs. The alkyl chain length of EFEs significantly influenced the antibacterial activity and EM showed the highest activity with minimum inhibitory concentrations ranging from 0.09 to 0.6 mM against Gram-positive bacteria. All EFEs exhibited radical scavenging activity and lipid oxidation inhibitory activity in oil-in-water emulsions, while the optimal alkyl chain for the antioxidative activity was observed in erythorbyl palmitate (C16:0). These findings will contribute to the practical applications of EFEs in food industry and the systematic investigation on the structure-properties relationships of other amphiphilic compounds. Graphical abstract: Image 1 Highlights: Alkyl chains affected the multi-functionality of erythorbyl fatty acid esters (EFEs). Among EFEs, erythorbyl myristate showed the best interfacial properties. The highest antibacterial activity was observed in erythorbyl myristate. Erythorbyl palmitate was the most effective antioxidant among EFEs.